Abdominoplasty after massive weight loss. Safety preservation fascia technique and clinical outcomes in a large single series-comparative study - Cannistrà, Claudio; Lori, Eleonora; Arapis, Konstantinos; Gallo, Gaetano; Varanese, Marzia; Pironi, Daniele; De Luca, Alessandro; Frusone, Federico; Amabile, Maria Ida; Sorrenti, Salvatore; Gagliardi, Federica; Tripodi, Domenico (Frontiers in Surgery, 2024)
Introduction Weight loss after bariatric surgery causes very important modifications to the patient's silhouette. Abdominal fat and skin excess reduction are associated with several complications. The most frequent are seroma and hematoma whereas major complications, such as pulmonary embolism, are less frequent. This study aimed to describe our technical procedure for abdominoplasty in patients with massive weight loss after bariatric surgery. Methods In total, 196 patients were included. All patients who underwent abdominoplasty classic (group A) and abdominoplasty with the preservation and lift of Scarpa fascia (group B) and with umbilical transposition between May 2018 and May 2021 were included. Patients with concomitant correction of ventral hernia were excluded. Demographic and operative data were analyzed according to comorbidities and postoperative complications. Results There were 160 (81.6%) women. The mean age was 43.6 years; the mean weight was 86.7 kg; and the mean BMI was 28.6 kg/m2. Five patients (2.5%) presented postoperative seroma. Four patients (2%) presented partial dehiscence/skin necrosis one of them requiring a revision. Finally, 26 patients presented a postoperative complication, with an overall incidence of 12.6%. The average postoperative hospital stay was 3.6. The rates of seroma were significantly higher in men, patients with a BMI > 30 kg/m2, and aged >50 years. Conclusion Preserving Scarpa Fascia during surgical post-bariatric patient procedures reduces the seroma formation and the scar complication and reduces the tension of the inguinal-pubic region with correction of our deformation after weight loss. Improves reducing the drain and reducing seroma incidence suction and hospital stay.